Green consciousness and consumer buying behaviour in a developing country: a study of Ghanaian consumers - Tawiah, Harriet Astra (KNUST, 2024)
A thesis submitted to the Department Of Marketing And Corporate Strategy, School Of Business, KWAME NKRUMAH UNIVERSITY OF SCIENCE AND TECHNOLOGY, in partial fulfillment of the requirement for the award of masters degree of Masters of business administration